Politik Gender dan Otonomi Daerah: Upaya Pemenuhan Hak Perempuan Nelayan di Desa Sei Nagalawan - Fernanda Putra Adela; Zakaria Zakaria; Nurlela Nurlela; Adil Arifin (Universitas Medan Area, 2019)
This paper discusses the problems experienced by fishermen's wives in Sei Nagalawan Village who experience social bias. Social bias in the sense of a paradox situation, where women experience a paradoxical situation that is when their husbands go to sea to catch fish. Automatically the responsibilities in the family are held by their wives. Not only that, the fishermen's wives also regularly catch fish on the shore. However, until now these women were not considered fishermen which resulted in them not being able to get health insurance and access to borrow money from the Bank. Not only the role of fishing women in the social, economic and environmental fields in activities against poverty. The author combines the Marxist, Phenomenological and Ethnometodological perspectives in countering the phenomenon of discrimination in his position as a female fisherman amid the workload that can reach 18 hours per day. At the end of this paper the author describes how the strategies of fishing women in Sei Nagalawan Village fight poverty by actively catching fish on the shore, developing Kampung Nipah ecotourism through the Muara Maimbai Multipurpose Cooperative, developing MSMEs by selling mangrove (mangrove) raw materials and actively conducting struggle activities to fulfill the recognition of women as fishermen. Because, according to Law Number 7 of 2016 concerning Protection and Empowerment of Fishermen, Fish Cultivators and Salt Farmers, fishermen are a type of work related to fishing.